2018
DOI: 10.1097/jcn.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Self-care Moderates the Relationship Between Symptoms and Health-Related Quality of Life in Heart Failure

Abstract: In HF, HRQOL is dependent on both the severity of physical and depressive symptoms and the level of engagement in HF self-care behaviors. Future research should consider both self-care behaviors and symptoms when examining patient HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
4
46
0
3
Order By: Relevance
“…When HF patients had poor self-care practice their quality of life become worse. This finding is consistent with other similar studies report, heart failure patients who had poor selfcare engagement had worse HRQOL (18,24,30,34,36,37). Kessing et al (30) also reported that lower self-care was associated not only with the overall HRQOL but also with physical and emotional subcomponents of quality of life.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When HF patients had poor self-care practice their quality of life become worse. This finding is consistent with other similar studies report, heart failure patients who had poor selfcare engagement had worse HRQOL (18,24,30,34,36,37). Kessing et al (30) also reported that lower self-care was associated not only with the overall HRQOL but also with physical and emotional subcomponents of quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…Heart failure patients' HRQOL is dependent on the patients' level of engagement in self-care behaviors (18). Self-care behavior is a modifiable factor that emphasizes the actions to be taken by HF patients to maintain life, healthy functioning and to improve the overall HRQOL (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have focused on medical correlates of QOL, with little attention to the potential influence of psycho-behavioral characteristics. For example, self-efficacy and self-care management are two factors that are modifiable and have been found to moderate the effects of chronic illness on QOL [ 52 , 53 ], yet this relationship has not been examined in patients with cancer-related LEL. These and other potentially modifiable factors need to be assessed and identified to allow for their inclusion in future strategies aimed towards improving QOL and psychosocial well-being within this understudied population.…”
Section: Discussionmentioning
confidence: 99%
“…These are depression, functional status, and HF knowledge, and the literature shows that they all play a key role in determining the self-care behavior of persons with HF. Depression is a major determinant of health-related quality of life in persons with HF [ 18 ]. Depression was evaluated using the Patient Health Questionnaire–9 (PHQ-9) [ 19 ], which is composed of nine items that ask about the frequency of problems patients suffered in the last 2 weeks.…”
Section: Methodsmentioning
confidence: 99%